Beyond the status quo, centring women in the Westminster system in the Commonwealth Caribbean: a preliminary analysis. Issue 1 (2nd January 2015) - Barrow-Giles, Cynthia
Abstract : Globally women form a small minority of national parliaments and continue to face a number of obstacles in their struggle for greater political equality and indeed the Commonwealth Caribbean is no different. I argue that the culture of political parties and Westminster institutional arrangements not only fail to create the political opportunity structure that would enable women to participate more fully in political life but also constrain their ability to change the agenda setting. The article begins with a cursory discussion of the state of democracy in the Commonwealth Caribbean, reviews the debate on the need for gender equality and sets the context of the Commonwealth Caribbean by way of a brief discussion of the participation of women in politics. It acknowledges the persistence of male-dominated political institutions and the continuation of a political culture within political parties that does little to encourage women's political participation. The final section of the paper reviews the attempts to bring legislative reform on such issues as domestic violence and sexual harassment.